Tantangan Berkelanjutan: Problematika Guru dalam Penerapan Kurikulum Merdeka Pada Mata Pelajaran Sejarah - Anggriani, Nurul Mila; Putro, Herry Porda Nugroho; Sriwati, Sriwati (Prabayaksa: Journal of History Education, 2024)
The Merdeka Curriculum represents an evolution from the 2013 Curriculum, introducing several changes aimed at providing schools, teachers, and students with opportunities to innovate, improvise, and negotiate for independent and creative learning. This research aims to investigate the implementation of the Merdeka Curriculum, highlighting challenges and efforts in teaching history. The research methodology utilized is descriptive qualitative, employing data collection techniques such as observation, interviews, and document analysis. Data analysis involves data reduction, presentation, and drawing conclusions, with validity ensured through measures of credibility, transferability, dependability, and confirmability. The findings reveal that Vocational High School 2 Banjarmasin has adopted the Merdeka Curriculum since 2021, emphasizing learning to generate products and services. Intracurricular learning is categorized into regular classroom sessions and extracurricular learning activities. The Project to Strengthen the Profile of Pancasila Students (P5) is conducted for a month outside regular teaching hours, with teachers independently preparing teaching materials. Teachers encounter various challenges in implementing the Merdeka Curriculum, including difficulties in analyzing learning outcomes, formulating learning objectives, constructing the flow of learning objectives, developing teaching modules, and selecting appropriate teaching media and methods. Additionally, limitations in technology, student textbooks, and classroom space contribute to these challenges. Efforts to address the obstacles in implementing the Merdeka Curriculum involve collective commitment, specialized training such as upskilling sessions and subject teacher collaboration activities, as well as enhancements to educational facilities and infrastructure. In conclusion, teachers must adapt to curriculum changes, overcome implementation obstacles, and possess the flexibility to ensure the effectiveness of curriculum implementation at Vocational High School 2 Banjarmasin.